Potential drug interactions in the Alcohol and Drug Psychosocial Care Center in a Northeastern Brazilian capital (Research, Society and Development, 2021)
Introduction: Mental disorders represent today one of the main challenges on the health agenda, both in developed and developing countries, constituting an important burden for public services. Objective: To evaluate potential drug interactions in a Psychosocial Care Center for Alcohol and Drugs, in São Luís. Method: This is a descriptive cross-sectional study, with a quantitative approach, carried out through the analysis of medical records of users of the Psychosocial Care Center in the period from May 2015 to March 2016. Potential drug interactions were identified and classified according to the drugs.com and Micromedex® database into mild, moderate, severe. Results: The study was carried out with 60 medical records of patients undergoing treatment at the CAPS-ad, 83% male and 17% female, with a mean age of 39.62 years for men and 37.7 years for women and 63% of the medical records pointed to the group of mental and behavioral disorders due to the use of multiple drugs and the use of other psychoactive substances. Among the analyzed records, 42 showed the possibility of drug interactions, being 1% mild, 80% moderate and 19% severe; 40% at risk of respiratory and central nervous system depression and 12% at risk of decreased pharmacological action by enzymatic induction of carbamazepine. Conclusion: The study revealed a high number of potential drug interactions that can compromise the clinical conditions of the patient and/or their treatment, thus revealing the importance of the health team's clinical performance.